SAT-433 The Influence of Thyroid Autoimmunity on Pregnancy Outcome in Infertile Women - Takeshima, Ken (J Endocr Soc, 2020)
Background: Women with subclinical hypothyroidism (SCH) and thyroid autoimmunity (TAI) reportedly have high risks of miscarriage and preterm birth. Infertile women undergoing assisted reproductive technology (ART) are recommended for levothyroxine (L-T4) supplementation to maintain TSH levels below 2.5 mIU/mL according to ATA guideline; however, insufficient evidence exists to determine whether L-T4 treatment for infertile women with TSH levels between 2.5 and 5.0 mIU/mL. Objective: To clarify the influence of TAI on pregnancy in infertile women under L-T4 treatment to maintain TSH levels below 2.5 mIU/mL, and to compare its influence depending on fertility treatments. Methods: A total of 595 infertile women who visited a fertility clinic between January 2013 and December 2015 were prospectively recruited to this study. Five patients with Graves’ disease were excluded and remained 590 women were included in the analysis. Infertile women with TSH levels above 2.5 mIU/mL were treated with L-T4 followed by evaluation of fertility status and pregnancy outcomes. Factors affecting pregnancy were analyzed statistically depending on fertility treatments. Written informed consent was obtained from all patients, and the study protocol was approved by the Ethics Committee. Results: The proportion of SCH and thyroid peroxidase antibodies (TPOAb).positivity was 19.6% and 10.4%, respectively. Women who did not become pregnant were older than those who became pregnant (p=0.003), but no influence of thyroid-associated factors on pregnancy was confirmed. Pregnancy outcome contrarily showed that women who had a miscarriage were older (p<0.001) and higher TPOAb titers (p=0.038) than those who had a live birth. In addition, higher age (OR 26.4, p<0.001) and high TPOAb titer (OR 11.8, p=0.043) were decided as risk factors for miscarriage through multiple logistic regression analysis. Among women who treated with intrauterine insemination, TPOAb titers were higher in women who had a miscarriage than in those who had a live birth (p=0.040). We further focused on the difference between ART methods including in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). Women undergoing IVF had higher TPOAb titers in women who had miscarriage than those who had a live birth (p=0.023), but in women undergoing ICSI there was no association between TPOAb titers and pregnancy outcome. Conclusion: Infertile women with high TPOAb titers are susceptible to miscarriage despite appropriate L-T4 treatment. The influence of TPOAb titers as well as TPOAb positivity on pregnancy should be considered, when undergoing fertility treatments.